Academic integration in higher education: A review of effective institutional strategies and personal factors - Abdul-Rahaman, Nurudeen; Arkorful, Vincent E.; Okereke, Tochukwu (Frontiers in Education, 2022)
Globally, there has been a surge in international students, posing challenges to their host institutions. The review aimed to identify institutional strategies and personal factors that promote international students' academic integration. With an independent systematic review of titles, abstracts, and full texts, 64 studies were sampled and analyzed. The study presented findings through a narrative synthesis across all studies. The review results showed that there have been an increasing number of studies on academic integration over the last decade. Institutional strategies like staff and student interaction, student orientation programs, classroom organization, supervisory support, and learning communities are more effective in promoting healthy academic lives and the academic progress of students. Personal factors, which include financial status, language ability, and self-efficacy in students, were revealed to facilitate healthy acamdemic lives and progress on campus. Prioritizing international students' welfare, providing language adaptation support, and increasing the accessibility of academic staff were suggested strategies for improving the academic lives of international students. The study also recommends that tertiary education systems and other stakeholders take these institutional strategies and personal factors into account when developing higher education policies. This will help international students have better academic lives and stay in school.